An analysis of urban public space in three European cities : London, Dublin and Amsterdam - Lawton, Thaddeus Philip (Trinity College (Dublin, Ireland). Department of Geography, 2009)
This thesis sets out to enquire into the relationship between recent urban transformation and urban public space in three European cities: London, Dublin and Amsterdam. This involves an analysis of the manner in which public space is produced in an official capacity and the way in which it is interpreted and used in everyday life. A central objective of the thesis is to examine the degree to which official ideals related to public space have been transferred between different urban contexts, and its consequences. Moreover, it also examines the importance of social context in terms of understanding urban public space.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin